2017
DOI: 10.3390/ijerph14020181
|View full text |Cite
|
Sign up to set email alerts
|

Family Environment and Childhood Obesity: A New Framework with Structural Equation Modeling

Abstract: The main purpose of the current article is to introduce a framework of the complexity of childhood obesity based on the family environment. A conceptual model that quantifies the relationships and interactions among parental socioeconomic status, family food security level, child’s food intake and certain aspects of parental feeding behaviour is presented using the structural equation modeling (SEM) concept. Structural models are analysed in terms of the direct and indirect connections among latent and measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 60 publications
(69 reference statements)
3
40
1
2
Order By: Relevance
“…Contrary to what was expected, family profiles did not differ according to their SES, as previously reported by several authors, e.g., [ 25 , 71 , 72 , 73 , 74 ]. Nevertheless, findings from the present study are in line with research that shows that higher HEI scores are associated with higher food expenditure [ 56 , 75 ], which is associated with the higher relative cost of healthy foods [ 14 , 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 66%
“…Contrary to what was expected, family profiles did not differ according to their SES, as previously reported by several authors, e.g., [ 25 , 71 , 72 , 73 , 74 ]. Nevertheless, findings from the present study are in line with research that shows that higher HEI scores are associated with higher food expenditure [ 56 , 75 ], which is associated with the higher relative cost of healthy foods [ 14 , 75 , 76 , 77 ].…”
Section: Discussionsupporting
confidence: 66%
“…It is often conceptualised as a combination of financial, occupational and educational influences. 8 The level of SES can partly explain the risk at birth outcome, 9 children’s anthropometric status 10 and neurodevelopment. 11 The risk of SGA was higher in the lower SES groups compared with the highest SES group in Finland, 12 Australia, 13 Japan 9 and others.…”
Section: Introductionmentioning
confidence: 99%
“…Family environment and parental characteristics are well-known determinants of both obesity and HRQoL in the early years of life [20,21]. Previous studies conducted in Iran have also reported the importance of various parental factors including parental age, educational level, employment, and weight status on overweight and obesity among children [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%